Salt-tolerant printing thickening agent and synthesis method thereof
By using multifunctional organic molecules and six -yuan metamorphosis hydrophilic dysfunction, combined with specific emulsification and trigger treatment, the salt -resistant printed thickener is prepared to solve the structural integrity of existing thickeners under the action of electrolytes. The problem has significantly improved its water holdings and anti -electrolyte performance.
Patent Information
- Application Number
- CN202411887800.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-21
AI Technical Summary
The existing anionic synthetic thickeners are difficult to maintain structural integrity under the action of electrolytes, resulting in disadvantages such as poor electrolytic resistance, poor thixotropy of color paste, poor water holding capacity, and easy edge smear.
Multifunctional organic molecules are used as functional monomers, combined with macromolecular hydrophilic functional agents containing six yuan rings, and prepare a salt -resistant printed thicker through specific emulsification and trigger treatment. This method enhances the water hug and anti -electrolyte performance of thickened agent by forming multi -hydrogen bonding and using strong static exclusion power.
It significantly improves the water hug and anti -electrolyte performance of the thickener, and enhances its stability and thickening effect in the electrolyte environment.
Smart Images

Figure SMS_3 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The invention relates to a salt-resistant printing thickener and a synthesis method thereof, belonging to the technical field of printing and dyeing. Background Art
[0002] Pigment printing has the advantages of simple process, fast production cycle, less sewage discharge, low production cost, and complete color spectrum. Pigment printing paste is usually composed of coating, adhesive, thickener and other additives. Among them, the thickener can increase the viscosity of the system and maintain its stable hydrophilic properties. Its performance plays a vital role in the printing effect. The thickeners currently used on the market are generally synthetic thickeners. Synthetic thickeners are divided into anionic and cationic types. Pigment printing generally uses anionic synthetic thickeners. Anionic synthetic thickeners have the advantages of high color yield, low solid content, easy production, and low cost. However, due to the complexity of the medium environment during the printing operation, the electrolytes present in the medium often destroy the hydrogen bonds or other non-covalent interactions between the thickener molecules, which ultimately makes it difficult for the thickener to maintain structural integrity under the action of electrolytes. Therefore, they generally have the disadvantages of poor electrolytic resistance, poor thixotropy of the paste, poor water holding capacity, and easy edge seepage. Summary of the invention
[0003] In order to solve the problems in the above background technology, the present invention provides a salt-resistant printing thickener and a synthesis method thereof.
[0004] A method for preparing a salt-resistant printing thickener in the technical solution for achieving the purpose of the present invention is as follows: S1: preparing an anionic monomer, a functional monomer, a chelating agent, and a chain transfer agent into an aqueous solution and adjusting the pH to obtain an aqueous phase; S2: adding solvent oil, composite emulsifier, and hydrophobic functional cross-linking agent into a reaction container and stirring to form an oil phase; S3: mixing the water phase and the oil phase and emulsifying them to obtain an emulsion; S4: adding an oxidant to the emulsion for deoxygenation treatment, then adding an initiator for reaction, and then cooling the emulsion to obtain the thickener; The functional monomer is a multifunctional organic molecule, and the functional group of the multifunctional organic molecule includes a carbon-carbon double bond and a morpholine group; The hydrophobic functional cross-linking agent is a macromolecule containing a six-membered ring.
[0005] The initiator is added all at once.
[0006] The functional monomer of the present application adopts a multifunctional organic molecule, whose functional group contains a carbon-carbon double bond and a morpholine group. Its function has a six-membered ring structure. The number of hydrogen bond acceptors in the six-membered ring structure is two, and a double hydrogen bond is formed inside the molecule, which increases the binding force between the thickener and the water molecules, so that the thickener as a whole obtains better water-holding performance.
[0007] The hydrophobic functional agent in the present application is a macromolecular component, and the cross-linking point of the hydrophobic functional agent has a rigid group such as a hexacyclic ring. When the cross-linking agent is in the water molecule, its polymer chain is fully extended, and the cross-linking point is in a stretched state. The negative charge on the polymer chain will produce a greater electrostatic repulsion force than other structures, and the conformation of the cross-linking point of the macromolecular chain changes, and a balance is reached between the electrostatic repulsion of the macromolecule and the resilience of the cross-linking point. The common ion effect of ordinary hydrophobic functional agents can reduce the negative charge density on the macromolecular chain, reduce the electrostatic repulsion, and the resilience of the cross-linking point of the hydrophobic functional agent is greater than the electrostatic repulsion, and the macromolecular chain shrinks from the stretched state to the curled state; the hydrophobic functional agent of the present application introduces a rigid group at the cross-linking point, which can effectively hinder the viscosity reduction phenomenon caused by the rebound curling of the macromolecular chain, so its anti-electrolyte effect is stronger.
[0008] The thickener prepared by the preparation method of the present application has stronger water-holding capacity and electrolyte resistance. The enhancement of its water-holding capacity promotes the enhancement of electrolyte resistance. By adopting the above structure, a tighter hydration layer can be formed under the action of multiple hydrogen bonds. At the same time, the strong electrostatic repulsion of the hydrophobic functional macromolecular components is used to reduce the interference of salt ions on the thickener, thereby improving its thickening effect.
[0009] As a preferred embodiment of the present invention, considering the availability of raw materials and the synthesis cost, the anionic monomer in step S1 is one or more of acrylic acid, ethyl acrylate, ethyl methacrylate, 2-acrylamide-2-methylpropanesulfonic acid, and maleic anhydride; the chelating agent is one or more of sodium citrate, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium gluconate, and sodium tripolyphosphate; the chain transfer agent is one or more of sodium benzoate, sodium hypophosphite, sodium bisulfite, sodium formate, sodium acetate, and n-butanol; the functional monomer is one of the following, wherein R1 is one of -CH2-, –CH2-CH2-, and –CH2-CH2-CH2-; R2 is one of -CH2-, –CH2-CH2-, and –CH2-CH2-CH2-; and R3 is one of -CH2-, –CH2-CH2-, and –CH2-CH2-CH2-.
[0010] As a preferred embodiment of the present invention, in order to improve the stability of the charge interface film during the emulsification process, prevent agglomeration during the emulsification process from affecting the fluidity and processing performance during the emulsification process, improve the chemical stability and storage stability of the thickener final product, and obtain a more reasonable molecular weight distribution range to control the binding force between the thickener and the working environment, the anionic monomer in step S1 accounts for 30%-45% of the total weight of the emulsion in S3; the functional monomer accounts for 1%-5% of the total weight of the emulsion in S3; the chelating agent accounts for 0.01%-0.03% of the total weight of the emulsion in S3; and the chain transfer agent accounts for 0.005%-0.02% of the total weight of the emulsion in S3.
[0011] As a preferred embodiment of the present invention, in order to improve the stability of the emulsion and achieve effective dispersion of the thickener component, the solvent oil in step S2 is 120 # Gasoline, 200 # Gasoline, kerosene, 5 # The invention discloses a kind of white oil; the composite emulsifier is at least two of SPAN-80, SPAN-60, TWEEN-81 and TWEEN-61; the hydrophobic functional crosslinking agent is one or more of 4,4-diphenylene dimethacrylate, 1,4-diacryloylpiperazine, butyl terephthalate and 1,3-adamantanediol diacrylate.
[0012] As a preferred embodiment of the present invention, in order to adjust the stability and good compatibility between the components, the solvent oil in step S2 accounts for 20%-30% of the total weight of the emulsion; the composite emulsifier accounts for 2.0%-3.5% of the total weight of the emulsion, and its HLB value is 6.0-8.0; the hydrophobic functional cross-linking agent accounts for 1%-4% of the total weight of the emulsion.
[0013] As a preferred embodiment of the present invention, the emulsification method in step S3 is a high-speed shear machine emulsification method. During the emulsification process, the viscosity of the emulsion is controlled to be 800-1500 mPa.S. Within this range, the particle size of the droplets in the emulsion can be effectively controlled, making the particles smaller and more uniform, thereby improving the stability and performance of the emulsion.
[0014] As a preferred embodiment of the present invention, in order to utilize free radicals to initiate the polymerization reaction between monomers and increase the reaction rate, the oxidant in step S4 is one or more of potassium persulfate, sodium persulfate, ammonium persulfate, and tert-butyl hydroperoxide; and the initiator is sodium pyrosulfate.
[0015] The above-mentioned reagents are added in the following manner: after 30 minutes of pre-oxidation, the oxidant is added at one time, and then the initiator sodium pyrosulfate is added dropwise.
[0016] As a preferred embodiment of the present invention, the amount of oxidant used in step S4 is 0.01%-0.05% of the weight of the emulsion, the concentration is 1%, and the amount of initiator added is until the temperature of the emulsion begins to rise, and the addition method is: while the reaction is being carried out, the initiator is added until the reaction temperature no longer changes, at which time the system no longer releases heat and the reaction is terminated. Controlling the initiator within this range can provide sufficient free radicals, which can effectively stimulate the reaction while preventing excessive polymerization due to excessive free radicals.
[0017] As a preferred embodiment of the present invention, in order to control the reaction process, the oxidant in step S4 is added all at once; initiation is carried out by dropwise addition and the reaction temperature is controlled below 50°C, and the reaction is considered to be completed when the temperature of the reactants no longer changes.
[0018] The invention also provides a salt-resistant printing thickener, which is prepared by any of the above methods.
[0019] By adopting the above technical solution, the present invention has the following beneficial effects: (1) The functional monomer of the present application adopts a multifunctional organic molecule. The functional group of the multifunctional organic molecule contains a carbon-carbon double bond and a morpholine group, and has a six-membered ring structure. The number of hydrogen bond receptors of the six-membered ring is two, and a double hydrogen bond is formed inside the molecule, which increases the binding force between the thickener and the water molecules, so that the thickener as a whole has better water-holding performance; the hydrophobic functional agent in the present application is a macromolecular component, and its cross-linking point has a rigid group such as a six-membered ring. When the cross-linking agent is in the water molecule, its polymer chain is fully extended, and the cross-linking point is in a stretched state. The negative charge on the polymer chain will produce a greater electrostatic repulsion force than other structures, and the conformation of the cross-linking point of the macromolecular chain changes, and a balance is achieved between the electrostatic repulsion of the macromolecule and the resilience of the cross-linking point. The common ion effect of ordinary hydrophobic functional agents can reduce the negative charge density on the macromolecular chain and reduce the electrostatic repulsion. The rebound force of the cross-linking point is greater than the electrostatic repulsion, and the macromolecular chain shrinks from a stretched state to a curled state; the hydrophobic functional agent of the present application introduces a rigid group at the cross-linking point, which can effectively hinder the viscosity reduction phenomenon caused by the rebound and curling of the macromolecular chain, so its anti-electrolyte effect is stronger; the printing thickener prepared by the preparation method of the present application has stronger water holding capacity and electrolyte resistance, and there is a promoting and enhancing effect between water holding capacity and electrolyte resistance. A tighter hydration layer can be formed under the action of multiple hydrogen bonds, and the strong electrostatic repulsion of the hydrophobic functional macromolecular component is used to reduce the interference of salt ions on the thickener, thereby improving the thickening effect.
[0020] (2) This application specifies the range of raw materials taking into account the availability of raw materials and synthesis costs.
[0021] (3) In order to improve the stability of the charge interface film during the emulsification process, prevent agglomeration during the emulsification process that affects the fluidity and processing performance during the emulsification process, and improve the chemical stability and storage stability of the thickener final product, the present application limits the content of the ingredients.
[0022] (4) In order to improve the stability of the emulsion and achieve effective dispersion of the thickener component, the solvent oil was selected in this application.
[0023] (5) In order to adjust the stability and good compatibility between the components, the content ratio of solvent oil, composite emulsifier and hydrophobic functional cross-linking agent is adjusted in this application.
[0024] (6) The present application effectively controls the particle size of droplets in the emulsion, making the particles smaller and more uniform, improving the stability and performance of the emulsion, and specifies the emulsification method and emulsion viscosity.
[0025] (7) This application specifies the types and amounts of oxidants and initiators to be added, effectively utilizing free radicals to initiate polymerization reactions between monomers and increase the reaction rate.
[0026] (8) The present application controls the method and speed of adding the oxidant, which can effectively stimulate the reaction while preventing the problem of excessive polymerization.
[0027] (9) The present application also provides a salt-resistant printing thickener, which has better water-holding capacity and electrolyte resistance than general thickeners. DETAILED DESCRIPTION
[0028] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the data and appendices in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0030] Therefore, the following detailed description of the embodiments of the present invention provided in the attached table and the examples is not intended to limit the scope of the invention claimed, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1: S1: 30% acrylic acid, 1% N-allylmorpholine, 0.01% disodium ethylenediaminetetraacetate, and 0.01% sodium hypophosphite are prepared into an aqueous solution, and the pH of the aqueous solution is adjusted to 6.8 with 48% sodium hydroxide for use; S2: Add 25% solvent oil, 2.5% emulsifier (composed of SPAN80 and TWEEN 81, HLB value is 6.8), and 1% 1,4-diacryloylpiperazine into the reactor, stir evenly and prepare the oil phase for later use; S3: slowly pour the water phase prepared in S1 into the oil phase prepared in S2, and shear it into an emulsion by a high-speed shearing machine, wherein the viscosity of the sheared emulsion is controlled to be 1210 mPa.S; S4: Deoxygenate the above emulsion for 30 minutes, add 0.01% tert-butyl hydroperoxide to the emulsion at one time, control the initial reaction temperature to 15°C, slowly add 1% concentration of sodium pyrosulfate to initiate the reaction, and control the maximum temperature of the reaction to not exceed 50°C by cooling water. Without temperature control, the reaction temperature will no longer rise, and the reaction has been fully reacted. The material is cooled and discharged to obtain a salt-resistant printing thickener A1.
[0032] Example 2: S1: 35% acrylic acid, 2% N-allylmorpholine, 0.02% disodium ethylenediaminetetraacetate, and 0.02% sodium hypophosphite are prepared into an aqueous solution, and the pH of the aqueous solution is adjusted to 7.0 using 48% sodium hydroxide for use; S2: Add 25% solvent oil, 3.0% emulsifier (composed of SPAN80 and TWEEN 81, HLB value is 6.8), and 3% 1,4-diacryloylpiperazine into the reactor and stir evenly to prepare the oil phase for later use; S3: slowly pour the water phase prepared in S1 into the oil phase prepared in S2, and shear it into an emulsion by a high-speed shearing machine, wherein the viscosity of the sheared emulsion is controlled to be 1000 mPa.S; S4: Deoxygenate the emulsion for 30 minutes, add 0.02% tert-butyl hydroperoxide to the emulsion at one time, control the initial reaction temperature to 15°C, slowly add 1% sodium pyrosulfate to initiate the reaction, and control the maximum temperature of the reaction to not exceed 50°C by cooling water. Without temperature control, the reaction temperature will no longer rise, indicating that the reaction has been fully reacted. The material is cooled and discharged to obtain a salt-resistant printing thickener A2.
[0033] Example 3: S1: 28% acrylic acid, 2% ethyl acrylate, 1% N-allylmorpholine, 0.01% tetrasodium ethylenediaminetetraacetate, and 0.01% sodium hypophosphite are prepared into an aqueous solution, and the pH of the aqueous solution is adjusted to 7.0 with 48% sodium hydroxide for use; S2: Add 25% solvent oil, 2.5% emulsifier (composed of SPAN80 and TWEEN 81, HLB value is 6.8), and 1% butyl terephthalate into the reactor and stir evenly to prepare the oil phase for later use; S3: slowly pour the water phase prepared in S1 into the oil phase prepared in S2, and shear it into an emulsion by a high-speed shearing machine, wherein the viscosity of the sheared emulsion is controlled to be 1000 mPa.S; S4: Deoxygenate the emulsion for 30 minutes, add 0.01% tert-butyl hydroperoxide to the emulsion at one time, control the initial reaction temperature to 18°C, slowly add 1% sodium pyrosulfate to initiate the reaction, and control the maximum temperature of the reaction to not exceed 50°C by cooling water. Without temperature control, the reaction temperature will no longer rise, indicating that the reaction has been fully reacted. The material is cooled and discharged to obtain a salt-resistant printing thickener A3.
[0034] Comparative Example 1: S1: 30% acrylic acid, 0.01% disodium ethylenediaminetetraacetate, and 0.01% sodium hypophosphite are prepared into an aqueous solution, and the pH of the aqueous solution is adjusted to 6.8 with 48% sodium hydroxide for use; S2: Add 25% solvent oil, 2.5% emulsifier (composed of SPAN80 and TWEEN 81, HLB value is 6.8), and 1% 1,4-diacryloylpiperazine into the reactor, stir evenly and prepare the oil phase for later use; S3: slowly pour the water phase prepared in S1 into the oil phase prepared in S2, and shear it into an emulsion by a high-speed shearing machine, wherein the viscosity of the sheared emulsion is controlled to be 1210 mPa.S; S4: Deoxygenate the emulsion for 30 minutes, add 0.01% tert-butyl hydroperoxide to the emulsion at one time, control the initial reaction temperature to 15°C, slowly add 1% sodium pyrosulfate to initiate the reaction, and control the maximum temperature of the reaction to not exceed 50°C by cooling water. Without temperature control, the reaction temperature will no longer rise, indicating that the reaction has been fully reacted. The material is cooled and discharged to obtain a salt-resistant printing thickener B1.
[0035] Comparative Example 2: S1: 30% acrylic acid, 1% N-allylmorpholine, 0.01% disodium ethylenediaminetetraacetate, and 0.01% sodium hypophosphite are prepared into an aqueous solution, and the pH of the aqueous solution is adjusted to 6.8 with 48% sodium hydroxide for use; S2: Add 25% solvent oil and 2.5% emulsifier (composed of SPAN80 and TWEEN 81, HLB value is 6.8) into the reactor and stir evenly to prepare the oil phase for later use; S3: slowly pour the water phase prepared in S1 into the oil phase prepared in S2, and shear it into an emulsion by a high-speed shearing machine, wherein the viscosity of the sheared emulsion is controlled to be 1210 mPa.S; S4: Deoxygenate the above emulsion for 30 minutes, add 0.01% tert-butyl hydroperoxide to the emulsion at one time, control the initial reaction temperature to 15°C, slowly add 1% concentration of sodium pyrosulfate to initiate the reaction, and control the maximum temperature of the reaction to not exceed 50°C by cooling water. Without temperature control, the reaction temperature will no longer rise, and the reaction has been fully reacted. The material is cooled and discharged to obtain a salt-resistant printing thickener B2.
[0036] Comparative Example 3: S1: 30% acrylic acid, 0.01% disodium ethylenediaminetetraacetate, and 0.01% sodium hypophosphite are prepared into an aqueous solution, and the pH of the aqueous solution is adjusted to 6.8 with 48% sodium hydroxide for later use; S2: Add 25% solvent oil and 2.5% emulsifier (composed of SPAN80 and TWEEN 81, HLB value is 6.8) into the reactor and stir evenly to prepare the oil phase for later use; S3: slowly pour the water phase prepared in S1 into the oil phase prepared in S2, and shear it into an emulsion by a high-speed shearing machine, wherein the viscosity of the sheared emulsion is controlled to be 1210 mPa.S; S4: Deoxygenate the emulsion for 30 minutes, add 0.01% tert-butyl hydroperoxide to the emulsion at one time, control the initial reaction temperature to 15°C, slowly add 1% sodium pyrosulfate to initiate the reaction, and control the maximum temperature of the reaction to not exceed 50°C by cooling water. Without temperature control, the reaction temperature will no longer rise, indicating that the reaction has been fully reacted. The material is cooled and discharged to obtain a salt-resistant printing thickener B3.
[0037] Results and Analysis: Accurately weigh 2g of thickener, add 98g of distilled water, stir and add 3-4 drops of ammonia water, stir thoroughly to prepare a white slurry with a mass fraction of 2%.
[0038] The viscosity of the white slurry was measured using a Brookfield viscometer at a constant speed of 10 rpm (spindle No. 64) and 25°C.
[0039] Electrolyte resistance is expressed as viscosity retention rate. The viscosity of the thickener white paste with 0.05% NaCl (solid) added is measured, and the viscosity retention rate is defined as η 加NaCl后 / η 加NaCl前 Generally, the higher the viscosity retention rate, the better the electrolyte resistance.
[0040]
[0041] From the comparison of the data between samples A1, A2, A3 and B1, B2, B3 in the above table, it can be seen that the use of the formula in this application can make the printing thickener obtain better white paste viscosity and better viscosity retention rate, and its salt resistance is better than other solutions; From the data comparison of samples A1 and B1 in the table, it can be seen that the annual white paste of the prepared printing thickener will decrease due to the lack of functional monomers; From the data comparison of samples B1 and B2 in the above table, it can be seen that when the hydrophobic functional cross-linking agent is lacking, the viscosity retention rate of the product will decrease.
[0042] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for synthesizing a salt-tolerant printing thickener, characterized in that The following steps are involved: S1: preparing an anionic monomer, a functional monomer, a chelating agent, and a chain transfer agent into an aqueous solution and adjusting the pH to obtain an aqueous phase; S2: adding solvent oil, composite emulsifier, and hydrophobic functional cross-linking agent into a reaction container and stirring to form an oil phase; S3: mixing the water phase and the oil phase and emulsifying them to obtain an emulsion; S4: adding an oxidant to the emulsion for deoxygenation treatment, then adding an initiator for reaction, and then cooling the emulsion to obtain the thickener; The functional monomer is a multifunctional organic molecule, and the functional group of the multifunctional organic molecule includes a carbon-carbon double bond and a morpholine group; The hydrophobic functional cross-linking agent has a benzene ring or a six-membered ring or other rigid groups at the cross-linking point; In step S1, the anionic monomer is one or more of acrylic acid, ethyl acrylate, ethyl methacrylate, 2-acrylamide-2-methylpropanesulfonic acid, maleic anhydride, etc.; the chelating agent is one or more of sodium citrate, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium gluconate, sodium tripolyphosphate; the chain transfer agent is one or more of sodium benzoate, sodium hypophosphite, sodium bisulfite, sodium formate, sodium acetate, n-butanol; the functional monomer is one of the following, wherein R1 is one of -CH2-, –CH2-CH2-, and –CH2-CH2-CH2-; R2 is one of -CH2-, –CH2-CH2-, and –CH2-CH2-CH2-; and R3 is one of -CH2-, –CH2-CH2-, and –CH2-CH2-CH2-.
2. The method for synthesizing a salt-tolerant printing thickener according to claim 1, characterized in that: The anionic monomer in step S1 accounts for 30%-45% of the total weight of the emulsion in step S3; the functional monomer accounts for 1%-5% of the total weight of the emulsion in step S3; the chelating agent accounts for 0.01%-0.03% of the total weight of the emulsion in step S3; and the chain transfer agent accounts for 0.005%-0.02% of the total weight of the emulsion in step S3.
3. The method for synthesizing a salt-tolerant printing thickener according to claim 1, characterized in that: The solvent oil in step S2 is 120 # Gasoline, 200 # Gasoline, kerosene, 5 # The invention discloses a kind of white oil; the composite emulsifier is a combination of at least two of SPAN-80, SPAN-60, TWEEN-81 and TWEEN-61; the hydrophobic functional crosslinking agent is one or more of 4,4-diphenylene dimethacrylate, 1,4-diacryloylpiperazine, butyl terephthalate and 1,3-adamantanediol diacrylate.
4. The method for synthesizing a salt-tolerant printing thickener according to claim 1, characterized in that: In step S2, the solvent oil accounts for 20%-30% of the total weight of the emulsion; the composite emulsifier accounts for 2.0%-3.5% of the total weight of the emulsion, and its HLB value is 6.0-8.0; and the hydrophobic functional cross-linking agent accounts for 1%-4% of the total weight of the emulsion.
5. The method for synthesizing a salt-tolerant printing thickener according to claim 4, characterized in that: The emulsification method in step S3 is a high-speed shear machine emulsification method, and the viscosity of the emulsion is controlled to be 800-1500 mPa.S during the emulsification process.
6. The method for synthesizing a salt-tolerant printing thickener according to claim 1, characterized in that: The oxidant in step S4 is one or more of potassium persulfate, sodium persulfate, ammonium persulfate, and tert-butyl hydroperoxide, and the initiator is sodium pyrosulfate.
7. The method for synthesizing a salt-tolerant printing thickener according to claim 5, characterized in that: In step S4, the amount of oxidant used is 0.01%-0.05% of the weight of the emulsion, the concentration is 1%, and the amount of initiator added is until the temperature of the emulsion starts to rise.
8. The method for synthesizing a salt-tolerant printing thickener according to claim 5, characterized in that: In step S4, the oxidant is added all at once; the initiator is added dropwise and the reaction temperature is controlled below 50° C. When the temperature of the reactants no longer changes, the reaction is considered complete and no more initiator is added.
9. A salt-resistant printing thickener prepared by the method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Method for synthesizing electrolyte-resistant thickener by using inverse emulsion
CN101613433A
Polymer thickening agent and preparation method and application thereof
CN106543353A
Water-in-oil polymeric emulsion composition and method for manufacturing water-in-oil polymeric emulsion composition
CN108024937A
Temperature-resistant and salt-resistant multi-component polymerization thickening agent and preparation method thereof
CN113788911A